2017
DOI: 10.7860/jcdr/2017/25062.9936
|View full text |Cite
|
Sign up to set email alerts
|

Extra Articular Supracondylar Femur Fractures Managed with Locked Distal Femoral Plate or Supracondylar Nailing: A Comparative Outcome Study

Abstract: Nailing proved more cumbersome intraoperatively due to escalated operating time and blood loss and successive anterior knee pain necessitating implant removal but this detriment may be offset by an inclination towards earlier union. With Less Invasive Stabilization System (LISS), technical errors are more common and less forgiving and must be overcome with proper preoperative planning and intraoperative attention to detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
3
22
0
1
Order By: Relevance
“…Following the removal of duplicate studies, a total of 4472 studies were available for title and abstract screening (Figure 1). With our inclusion criteria applied and relevant reference lists screened, 117 studies 1,2,4,5,10,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the removal of duplicate studies, a total of 4472 studies were available for title and abstract screening (Figure 1). With our inclusion criteria applied and relevant reference lists screened, 117 studies 1,2,4,5,10,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 71 studies 2,10,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121 (60.7%) evaluated tibial plateau fractures, 16 studies 14,15,16,17,18,19,20,21,22,23,…”
Section: Resultsmentioning
confidence: 99%
“…Clinical research was performed to compare the efficacy of retrograde IMN (59 cases) and LISS plates (56 cases) in the treatment of distal femoral fractures. The results showed that the techniques were effective for type A fractures, with no significant difference in the implants, and revealed that the outcome largely depended on surgical technique rather than the choice of implant. Many scholars have evaluated the clinical efficacy of LISS plate in the treatment of distal femoral fractures, with clinical healing rates of 85%–100%.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical randomized prospective study compared the outcomes for LISS plate versus retrograde IMN in the management of extra articular supracondylar femur fractures, and indicated that the complication rates were equivalent between them. The retrograde IMN achieved earlier union as well as better functional outcomes, and it was suggested that surgical planning and expertise rather than the choice of implant were crucial for optimal results. LISS plate and retrograde IMN are universally adopted options for clinical treatment of comminuted femoral supracondylar fractures, and clinical results have demonstrated good clinical performance.…”
mentioning
confidence: 99%
“…Treatment of distal femoral fractures by minimally invasive percutaneous plate osteosynthesis (MIPPO) using anatomically contoured plates without direct exposure of the fracture fragments leads to better clinical outcomes compared with the traditional open reduction techniques; however, these submuscular plating methods are considered technically challenging. [1,2] Fitting the plate in the correct position while completion of alignment in all three axes can be cumbersome even to the experienced surgeons, and technical errors are not forgiving. [3] Reduction without using the plate is particularly challenging when performing minimally invasive surgery since bone exposure is very limited.…”
mentioning
confidence: 99%